ANALISIS KOMPARATIF PENDAPATAN USAHATANI KENTANG VARIETAS SUPERJOHN DAN VARIETAS GRANOLA L DI DESA PINASUNGKULAN UTARA KECAMATAN MODOINDING - Neni ., Nuraeni; Rine ., Kaunang; Lorraine W. Th. Sondak (AGRI-SOSIOEKONOMI, 2018)
The objective of this research is to know the comparison of Superjohn varieties and varieties of Granola L in Pinasungkulan Utara Village, Modoinding District. The location of the study was determined purposively (purposive sampling), the determination of the number of samples taken by census (Saturated Sampling) for farmers varieties Granola L as much as 20 farmers and 20 farmers Superjohn varieties taken simple random (Simple Random Sampling). The method of analysis used in this research is the analysis of farm income and komaparatif analysis by using t-test two samples Independent Sample T-test. The results showed that the average income of farmers Superjohn varieties is Rp.70.062.947,00 lower than the average income obtained by farmers varieties Granola L Rp.87.029.058,00. It can be seen that the average income difference between the two varieties is Rp.16.960.111,00. Based on statistical test results with MINITAB Program, the calculation of income per hectare obtained significant value of P-Value of 0.01 at Î± 5% that is 0,01 < 0,05. This means that H0 is rejected and H1 is tested for the fact that there is a significant difference between Superjohn varieties potato production income and Granola L varieties.